Effective post-graduate education of pharmacist with information technology - Bilai, I. M.; Mykhailiuk, Ye. O.; Tsys, O. V.; Білай, Іван Михайлович; Михайлюк, Євгеній Олегович; Цис, Олексій Вікторович (Czech Republic, Karlovy Vary: Skleněný Můstek, 2017)
The main objective of postgraduate education is to increase the level of practical training of graduates of medical (pharmaceutical) educational institutions, their professional readiness for self-employment. One of the ways to optimize this process is the use of a professionally-oriented approach to learning. The basic principles of organization professionally-oriented training are qualitative methodological support of educational process and their connection with the practical activity of future specialists of pharmacy. It is important to have consciously thinking pharmacists in making practical decisions. Therefore, the task of the pharmacists in this approach to learning is the acquisition new knowledge and formation of practical experience of their use, and the role of the teacher should be directed to the selection of tasks with professional content and to strengthen the self-reliance in their decision.